(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
A newly obtained foraminiferal assemblage from the Guadalupian−Lopingian, and Induan of the Western Salt Range (Pakistan) comprises 47 species (including 7 species of fusulinoideans) of 24 genera and 71 species (including 9 species of fusulinoideans) of 41 genera, in Nammal and Zaluch sections, respectively. Our results show that only 4 species went extinct during the Guadalupian−Lopingian mass extinction (GLME), suggesting the GLME was minor for smaller foraminifers in the Salt Range. Most species went extinct during the Permian-Triassic mass extinction (PTME), except the two survivor genera, Nodosinelloides and Planiinvoluta. During the end-Permian mass extinction, majorities of the species became extinct in lower part of Chhidru Formation, beacuse they are not tolerant to the terigenious-clastic input in the upper part of Chhidru Formation. The extinction process of foraminifers in the Nammal and Zaluch sections has been documented for the first time. Five foraminiferal assemblages are established in the shallow marine shelf deposits of Western Salt Range, i.e., Wordian Geinitzina araxensis assemblage in tide-influenced subaqueous delta to middle shelf environment, Capitanian Baisalina pulchra assemblage and Wuchiapingian Codonofusiella schubertellinoides assemblage in inner-outer shelf carbonate deposits, Changhsingian Colaniella pseudolepida assemblage and Induan Nodosinelloides-Planiinvoluta assemblage in mixed siliciclastic–carbonate shelf setting. The Baisalina pulchra and Codonofusiella schubertellinoides assemblages have wide geographic distribution and have been found in Transcaucasus, China, Turkey, Crimea and Oman. The other three assemblages (i.e., Geinitzina araxensis, Colaniella pseudolepida, and Nodosinelloides-Planiinvoluta assemblages) found in this study are likely local/regional assemblages. The foraminifers were observed with the standard microscopic system Leica-DM500. A total of 681 specimens of foraminifers are reported in the Zaluch Group and Mianwali Formation of Nammal and Zaluch sections. Five hundred ninety-nine smaller foraminifers specimens were recovered. Among the smaller foraminifera, Nodosinelloides, Pachyphloia, Geinitzina, Colaniella, Hemigordius, Tuberitina, and Langella are the most dominant genera. Larger foraminifera genera include Nankinella, Codonofusiella, Reichelina, Necdetina and Pisolina, represented by 82 specimens. A total of 3 classes (e.g., Nodosariata, Fusulinata, and Tubothalamea) and seven orders (i.e., Miliolida, Spirillinida, Lagenida, Parathuramminida, Endothyrida, Fusulinida, and Earlandiida) are identified in the current study. Among them, Lagenida becomes the most dominant by diversity and abundance. Shannon diversity and other indices rise progressively from Wordian to Changhsingian in the shallow marine sediments before dropping to zero in the Early Triassic mixed siliciclastic–carbonate shelf deposits.